Acute hepatitis due to Herpes simplex virus in an adult - Flewett, T. H. (1969)
A case is described of herpetic hepatitis in a pregnant woman with primary herpetic stomatitis. Intranuclear inclusion bodies and virus particles were found in hepatocytes, and herpes virus was isolated from a liver biopsy and from oral swabs but not from blood. From rising titres of neutralizing and complement-fixing antibody it is concluded that the oral infection was a primary one. Factors predisposing to the hepatitis are discussed.